2018
DOI: 10.3389/fvets.2018.00127
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Nanoparticles Enhance Brain Connectivity in the Canine Olfactory Network: Evidence From an fMRI Study in Unrestrained Awake Dogs

Abstract: Prior functional Magnetic Resonance Imaging (fMRI) studies have indicated increased neural activation when zinc nanoparticles are added to odorants in canines. Here we demonstrate that zinc nanoparticles up-regulate directional brain connectivity in parts of the canine olfactory network. This provides an explanation for previously reported enhancement in the odor detection capability of the dogs in the presence of zinc nanoparticles. In this study, we obtained fMRI data from awake and unrestrained dogs while t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 79 publications
0
10
0
Order By: Relevance
“…Subsequent studies have demonstrated that zinc nanoparticles function at the olfactory receptor level in the initial events of olfaction 3 , and a single metal nanoparticle binds two receptor molecules to form a dimer 4 . This olfactory enhancement was observed in young and mature mouse olfactory epithelial cultures, dissected rodent olfactory epithelium 2 , 3 , 5 , 6 , and live conscious dogs 7 , 8 .…”
Section: Introductionmentioning
confidence: 80%
“…Subsequent studies have demonstrated that zinc nanoparticles function at the olfactory receptor level in the initial events of olfaction 3 , and a single metal nanoparticle binds two receptor molecules to form a dimer 4 . This olfactory enhancement was observed in young and mature mouse olfactory epithelial cultures, dissected rodent olfactory epithelium 2 , 3 , 5 , 6 , and live conscious dogs 7 , 8 .…”
Section: Introductionmentioning
confidence: 80%
“…Although unexpected, these results might reflect dogs’ significantly higher olfactory sensitivity and it’s use to infer social and contextual information [54 for review]. However, the link between cognition and olfaction remains speculative since behavioural studies using olfactory cues so far mainly explored dogs’ odour and disease detection abilities (e.g., [8286] while dog imaging studies on olfaction focused on reward-processing [87,88] or general sensory abilities [8991]. However, a recent behavioural study investigating dog cognition using olfactory cues showed first evidence that dogs form representations of their owners when smelling their tracks [92].…”
Section: Discussionmentioning
confidence: 99%
“…Taking into account the number of drugs used in canine veterinary medicine, available studies have tested a less than representative number of substances for effects on canine olfaction. Even though zinc sulfate [ 53 ] has been used routinely in various studies for destruction of the main olfactory epithelium in many species [ 53 ], Ramaihgari et al [ 54 ] found that that zinc nanoparticles could potentially be used to increase canine detection capabilities in environments with very low concentrations of the odorants. Among the drugs used for anesthesia and analgesia in dogs, isoflurane and propofol, as well as fentanyl followed by naloxone, have been investigated in terms of olfaction capability in dogs, but no negative effect on canine olfaction was observed [ 55 , 56 ].…”
Section: Internal and Environmental Factors Influencing Olfactory Skills: Olfaction Gene Polymorphism Age Sex And Breed-specific Olfactormentioning
confidence: 99%